MAKNA SIMBOL TOR-TOR DAGANAK TUBU PADA MASYARAKAT ANGKOLA DI DESA PARSALAKANKECAMATAN ANGKOLA BARAT KABUPATEN TAPANULI SELATAN - PUTRI NORMA SARI (Universitas Negeri Medan, 2014)
This research constitute study about symbol meaning Tor torDaganakTubu on Angkola's society at Parsalakan village district West Angkola'sTapanuli southRegency. Tor torDaganakTubu this figure family thanksgiving while welcome childbirth. This Tor tor escort by song poem that is attributed use to good advantage babies.In this observational result is used each theory which supportive theories with observational topic amongst those cognitive meaning, symbol theory, structured theory, savvy Tor tor and custom ceremony savvy.Observational time that is utilized to work through about Tor torDaganakTubuthis up to two months, which is on month of November 2014 until January 2015. Observational place is at Parsalakan village district West Angkola'sTapanuli southRegency.Population on observational it is some bodies society custom chairman Angkola who gets place living at PadangsidempuanCity, custom ceremony promoter, kinsfolk and family as panortor.sample in observational it is 2 custom chairmen some bodies kinsfolk or party promoter families.Data collecting tech covers observation, interview, studi is bibliography and documentation, then analysis by descriptive kualitatifmethod.Base observational result that is done gets to be known that wholly symbol meaning that exists in Tor torDaganakTubuepitomizing thanksgiving form while welcome childbirth.In its movement exists curtsey meaning to God Lord Mighty and respect to fellow being, asking for goodness gives that invocation, and divides blessing,. Despitefully inende(song poem) available too meaning that corresponds withTor- tor. Keyword: Tor torDaganakTubu, Symbol meaning, Angkola's society